Tamanu Oil (Calophyllum inophyllum L.) Promotes Wound-Healing Activity in Alloxan-Induced Diabetic Rats, and Its Fatty Acids Profile - Rita Rakhmawati; Saptono Hadi; Ahmad Ainurofiq; Estu Retnaningtyas Nugraheni; Syaiful Choiri; Tiara Dewi Salindri Pratama (Universitas Sebelas Maret, 2024)
Diabetes Mellitus (DM) is a metabolic disease and is a severe threat because it causes diabetic wounds. Treating injuries in patients with DM is dominated by synthetic chemicals such as anti-inflammatory, corticosteroids, and antibacterial. It has side effects, so further exploration of natural ingredients is needed. One plant that has the potential to heal wounds is tamanu oil or nyamplung oil. This study aimed to investigate the effect of tamanu oil on the healing of diabetic wounds and the fatty acid composition profile. Male rats of the Wistar strain (Ratus novergius) were given incision wounds along a 2 cm depth of 2 mm, randomly divided into three groups, by applying topically twice a day. We are profiling fatty acids using gas chromatography-mass spectrometry (GC-MS). As far as we know, this is the first study showing that tamanu oil can speed up the healing of diabetic wounds in rats. The Tamanu oil containing oleic acid (42.65%), linoleic acid (25.69%), stearic acid (16.50%), and palmitic acid (12,93) had better effectiveness than other groups, demonstrated by wound closure exceeding 50% on day six and wound closure by 100% on day nine.